Orthostatic tolerance and training methodology in physically active men and women - Hayden W. Hess; Courtney E. Wheelock; David Hostler (PLoS ONE, 2026)
Previous studies suggest that training methodology alters orthostatic tolerance in elite and/or well-trained athletes. However, little is known about the effect of training methodology on orthostatic tolerance among the general physically active population. We tested the hypothesis that men and women participating in hybrid training (i.e., combined resistance and endurance training) would demonstrate superior orthostatic tolerance compared to aerobic endurance trained and recreationally active individuals. Twenty-nine participants were classified into one of the three groups depending on their current, self-reported training methodology. All participants reported at least 150 minutes per week of recreational activity (Recreationally Active Group; n = 10), hybrid training classes (Hybrid Group; n = 9), or endurance training (Endurance Group; n = 10) for ≥6 months. Anthropometrics (height and mass) were measured, and body composition was assessed via air displacement plethysmography. Orthostatic tolerance was assessed by a progressive lower-body negative pressure (LBNP) test and quantified via cumulative stress index (CSI). CSI did not differ between groups (p = 0.2542). Fat-free mass (FFM) was positively related to CSI (R² = 0.4092) and differed between groups (recreationally active: 56.1 ± 10.0 kg; hybrid: 65.5 ± 13.2 kg; endurance: 51.2 ± 10.5 kg; p = 0.0453). However, CSI normalized to FFM did not differ between groups (p = 0.6210; FFM missing for two participants). Among recreationally active adults, training methodology does not appear to modify orthostatic tolerance. Consistent with previous work, we report that body composition and anthropometrics are related to orthostatic tolerance highlighting the importance in maintaining lean mass regardless of training methodology.